The Quantum Theory of Atoms in Molecules and the Interactive Conception of Chemical Bonding - Esser, Stephen (Philosophy of science, 2019)
Quantum physics is the foundation for chemistry, but the concept of chemical bonding is not easily reconciled with quantum mechanical models of molecular systems. The quantum theory of atoms in molecules, developed by Richard F. W. Bader and colleagues, seeks to define bonding using a topological analysis of the electron density distribution. The "bond paths" identified by the analysis are posited as indicators of a special pair-wise physical relationship between atoms. While elements of the theory remain subject to debate, I argue that the quantum theory of atoms in molecules embodies a distinctive interactive conception of bonding that is an attractive alternative to others previously discussed.